Long-range prediction of monsoon onset over Kerala - RAJEEVAN , M.; DUBEY, D. P. (MAUSAM, 1995)
ABSTRACT. Using the data of 33 years ( 1961-1993) the effect of the intensity of heat low over central India during the Month of April and Winter (December to February) Eurasian snow cover on interannual variation of monsoon date over Kerala were examined. Composite mean surface temperature over central India during the month of April was higher during early onset years by 3.5° C. April mean surface temperature index (MST) and Winter (December to February) Eurasian snow cover (WSC) are significantly correlated with Monsoon onset dates al 1% and 5% significant levels respectively. Lower surface temperature and excessive snow cover indicate a late onset. A regression equation was developed for long range prediction of onset date over Kerala using MST and WSC as independent variables. The root mean square error (RMSE) of the relationship was found to be 4.6 days. The model was tested using independent data of five years and was found performing well. Contingency tables were developed between the pairs MOD and WSC and MOD and MST. The tables can be used for probability forecasts of early and late onset years.